Building Consumer Loyalty Through Digital Marketing Strategies in Anime Clothing Brands - Felix Sutisna; Tuti Nurhaeni; Nuke Puji Lestari Santoso; Galih Putra Cesna; Noah Rangi; Eka Dian Astuti (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
In the fashion industry, particularly within the anime clothing brand sector, building consumer loyalty has become a crucial challenge for ensuring long- term growth while supporting sustainability principles aligned with the Sustainable Development Goals (SDGs), specifically SDGs 8 and SDGs 12. This study aims to analyze various digital marketing approaches that can enhance consumer loyalty toward anime clothing brands by examining how digital interactions, visual identity, and community engagement contribute to sustained brand consumer relationships. The research employs a descriptive qualitative approach supported by observational data from social media analytics, documentation of digital campaign activities, and the interpretation of consumer engagement patterns across multiple digital platforms. The findings indicate that digital strategies such as leveraging social media to strengthen brand presence, collaborating with anime influencers, utilizing community based content, and implementing personalization through email marketing and loyalty programs effectively increase consumer emotional attachment and behavioral loyalty. Brands that successfully create emotionally engaging digital experiences and interact authentically with their audiences demonstrate a stronger potential to build sustainable loyalty. Furthermore, maintaining consistent brand com- munication, ensuring continuity in marketing campaigns, and integrating SDGs oriented values are identified as essential components for sustaining long-term relationships with consumers. The study concludes that digital marketing not only strengthens brand visibility but also plays a strategic role in shaping responsible consumer behavior, fostering loyalty within niche fashion communities, and supporting broader sustainability goals in the anime fashion industry.